Integration of the Gasing (Easy, Fun, and Enjoyable) Method with the Philosophical Values of Science in Primary Education - Putra, Kadek Ashadi; Jenuri, Jenuri (International Journal on Advanced Science, Education, and Religion, 2025)
The This study examines the GASING (Easy, Fun, and Enjoyable) method in mathematics education through the lens of the philosophy of science, which encompasses three fundamental dimensions: ontology, epistemology, and axiology. The research addresses four key questions: (1) What is the nature of mathematics learning through the GASING method from an ontological perspective? (2) How is the process of knowledge construction within the GASING method explained through an epistemological framework? (3) What axiological values are embedded in the implementation of the GASING method? and (4) How does the GASING approach align with the fundamental principles of the philosophy of science in the context of mathematics education? Drawing upon a literature review of 14 scientific articles, the findings reveal that the GASING method develops understanding progressively from concrete to abstract, forming a strong ontological foundation. It promotes active knowledge construction through meaningful learning experiences as an epistemological process, and it embodies key axiological values such as perseverance, collaboration, and enthusiasm for learning. Furthermore, GASING emerges as a pedagogical approach that holistically integrates ontological, epistemological, and axiological dimensions, thereby reflecting the principles of the philosophy of science. The study contributes to the field by positioning the GASING method not merely as a pedagogical strategy, but as a comprehensive scientific framework for mathematics learning. This integration underscores its potential to enhance conceptual understanding and character development in primary mathematics education.